Effect of deformation mode and grain size on Bauschinger behavior of annealed copper. (February 2016) - Mahato, Jayanta Kumar; De, Partha Sarathi; Sarkar, Abhijnan; Kundu, Amrita; Chakraborti, Pravash Chandra
Highlights: Bauschinger effect has been investigated with monotonic and ratcheting deformation. Back stress evolution is more in case of forward deformation by monotonic loading. For both deformation modes back stress is more in case of fine grained specimens. Bauschinger parameters depend on both back stress magnitude and unloading stress. Abstract: The present investigation looks into the effect of forward deformation mode, monotonic and cyclic, but asymmetric, on the Bauschinger phenomenon of annealed polycrystalline copper in terms of different Bauschinger parameters for 2.5–18% unidirectional tensile strain. Apart from the amount of deformation, the Bauschinger phenomenon has also been looked into as a function of stress rate used for forward deformation and also the grain size. It is found that Bauschinger effect is less pronounced when the forward deformation is carried out through asymmetric cyclic loading as compared to monotonic loading. This difference in the Bauschinger effect is attributed to lower back stress developed during asymmetric cyclic loading as compared to monotonic deformation. In the present investigation very negligible influence of stress rate on Bauschinger effect has been observed. On the other hand, for both monotonic and asymmetric cyclic deformation it is observed that Bauschinger effect is more in case of fine grain size.